Power Dynamics in Ahmad Tohari’s Novel “The Dancer” - Pritania Savitri (Passage, 2016)
This research concentrates on the interplay of power between the main character and other characters and the formation of the main character’s identity as a result of her social interaction with the members of society. To complete the data analysis, five basic tenets of Foucault’s theory of power (2006), Fundamental Nature of Power by Rummel (1976), and Theory of Identity Formation by Marcia (2005) are employed. This research highlights three major points as the finding of the data analysis which focuses on the main character protagonist, Srintil. First, the interplay of power between Srintil and other characters is considered as a strategy of interest and not being possessed by particular parties. Srintil’s active participation in exercising and resisting the power in her social interaction depicts that she is responsive and susceptible character. The previous finding leads to another conclusion that Srintil’s identity is dynamic and highly influenced and shaped from external factors within her social domain. Third, Srintil fails to identify herself as a result of lacking an understanding and anticipation of her expectation and society demands. According to the analysis, it can be deduced that young adult character’s identity is fluctuative and exceedingly affected by power relation in social interaction. Keywords: power, power relation, identity, identity formation, young adult literature